Reduction of carbon monoxide. Past research summary - Schrock, R.R. (Massachusetts Institute of Technology, 1981)
Research programs for the year on the preparation, characterization, and reactions of binuclear tantalum complexes are described. All evidence to date suggest the following of these dimeric molecules: (1) the dimer does not break into monomers under mild conditions; (2) intermolecular hydride exchange is not negligible, but it is slow; (3) intermolecular non-ionic halide exchange is fast; (4) the ends of the dimers can rotate partially with respect to one another. The binuclear tantalum hydride complexes were found to react with carbon monoxide to give a molecule which is the only example of reduction of CO by a transition metal hydride to give a complex containing a CHO ligand. Isonitrides also reacted in a similar manner with dimeric tantalum hydride. (ATT)